TAX COMPLEXITY: STRATEGIC TAX PLANNING FOR IMMIGRANT ENTREPRENEURS IN THE UNITED STATES - de Almeida, Alex Porto Alegre (Revista Sistemática, 2023)
Immigrant entrepreneurship has long played a vital role in the economic development of the United States, with foreign-born individuals demonstrating higher rates of business creation than native-born citizens. However, immigrant entrepreneurs face unique challenges when navigating the U.S. tax system. This article explores the importance of tax planning as a legal and strategic necessity for immigrant-founded businesses. It highlights key regulatory hurdles, such as entity classification, residency determination, and international financial disclosures, emphasizing the role of proactive planning in ensuring compliance and sustainability. Furthermore, the paper identifies support mechanisms and fiscal incentives available to mitigate risks and promote inclusive economic participation. Through a combination of empirical insights and policy analysis, the article underscores tax planning as not merely a compliance tool, but as a catalyst for immigrant entrepreneurial success in the United States.